Pengaruh Penggunaan Gadget dan Peran Orang Tua dalam Minat Belajar Anak Muda di Desa Karang Ketug - Agustin, Reza Ayu Nur; Pradikto, Sugeng (Yayasan Pendidikan Insan Mulia Utan Sumbawa, 2025)
This study aims to analyze the influence of gadget use and human behavior on the learning interests of the younger generation in Karang Ketug Village, Pasuruan City. Along with technological advances, the use of gadgets by children is increasing and can have both positive and negative impacts on the learning process. In addition, the role of adults as guides and motivators in children's education is very important to ensure the use of effective technology and increase learning motivation. This study uses a quantitative survey method approach. Data collection was carried out using a questionnaire given to 30 teenagers in Karang Ketug Village. The results of the analysis show that the use of gadgets has a significant influence on learning motivation, both positively through access to information and negatively through a lack of interest in subjects. In addition, the role of adults as guides and motivators in children's education is very important to ensure the use of effective technology and increase learning motivation. From the title above, I am researching the influence of gadget use and the role of parents on the learning interests of the younger generation in Karang Ketug Village, Pasuruan City. Here I learn about teenagers aged 12 to 17 years in Karang Ketug Village RT. 04 RW. 03 because Karang Ketug Village has many RTs, but I chose to conduct research in Karang Ketug Village, Pasuruan City.